limx→∞ cot−1⁡(x+1−x)sec−1⁡2x+1x−1x is equal to

limxcot1(x+1x)sec12x+1x1x is equal to

  1. A

    1

  2. B

    0

  3. C

    π2

  4. D

    non-existent

    Register to Get Free Mock Test and Study Material

    +91

    Verify OTP Code (required)

    I agree to the terms and conditions and privacy policy.

    Solution:

          limxcot1(x+1x)sec12x+1x1x

    =limxcot11x+1+xsec12+3x1x=cot1(0)sec1()=π/2π/2=1

    Chat on WhatsApp Call Infinity Learn

      Register to Get Free Mock Test and Study Material

      +91

      Verify OTP Code (required)

      I agree to the terms and conditions and privacy policy.